Comparative Evaluation of Structural Characteristics and in Vitro Biological Activities of Polysaccharides from Common Bean (Phaseolus vulgaris L.) and Those from Shiitake Mushroom (Lentinus edodes) - XU Mengyue, TIAN Xin, WANG Junke, WU Aoxue, ZOU Zhiyi, WU Jiahui, WANG Hongbo (Shipin Kexue)
In order to comprehensively evaluate the nutritional value of common bean polysaccharides, shiitake mushroom polysaccharides were used as the reference standard in this study. Fourier transform infrared spectroscopy (FTIR), high performance liquid chromatography (HPLC), high performance gel permeation chromatography (HPGPC), scanning electron microscopy (SEM) and Congo red assay were used to characterize the structures, monosaccharide compositions, molecular masses, and microstructures of the two kinds of polysaccharides. Their water solubility and water-holding capacity were compared, and their antioxidant, hypoglycemic and hypolipidemic activities in vitro were evaluated comprehensively. The results showed that the yield of common bean polysaccharides was significantly higher than that of shiitake mushroom polysaccharides, (7.01 ± 0.57)% versus (5.04 ± 0.38)% (P < 0.05), and the content of uronic acid in common bean polysaccharides was 2.21 times higher than that of shiitake mushroom polysaccharides. The major polysaccharide components of common bean and shiitake mushroom had molecular masses of 77.157 and 559.245 kDa, respectively. Common bean polysaccharides contained a small amount of esterified pectic polysaccharides with a loose and rough microstructure, while shiitake mushroom polysaccharides were heteropolysaccharides with a triple helical structure containing α- and β-pyran rings, which exhibited a compact and smooth microstructure. The water solubility and water-holding capacity of shiitake mushroom polysaccharides were 1.61 and 6.07 times higher than those of common bean polysaccharides, respectively. The in vitro antioxidant capacity, hypoglycemic activity and hypolipidemia activity of common bean polysaccharides were higher than those of shiitake mushroom polysaccharides, 2.43 versus 1.82. In conclusion, common bean is an ideal food resource for developing active polysaccharide products.